Relations between molecular cloud structure sizes and line widths in the large magellanic cloud - Wong, Tony; Glover, Simon; Klessen, Ralf S. (The astrophysical journal, 2019)
We present a comparative study of the size-line width relation for substructures within six molecular clouds in the Large Magellanic Cloud (LMC) mapped with the Atacama Large Millimeter/submillimeter Array. Our sample extends our previous study, which compared a Planck detected cold cloud in the outskirts of the LMC with the 30 Doradus molecular cloud and found the typical line width for 1 pc radius structures to be five times larger in 30 Doradus. By observing clouds with intermediate levels of star formation activity, we find evidence that the line width at a given size increases with increasing local and cloud-scale 8 μm intensity. At the same time, the line width at a given size appears to independently correlate with measures of the mass surface density. Our results suggest that both virial-like motions due to gravity and local energy injection by star formation feedback play important roles in determining intracloud dynamics.